Anti-RANKL treatment inhibits erosive joint destruction and lowers inflammation but has no effect on bone formation in the delayed-type hypersensitivity arthritis (DTHA) model. Issue 1 (December 2016) - Atkinson, Sara; Bleil, Janine; Maier, René; Kühl, Anja; Thorn, Mette; Serikawa, Kyle; Fox, Brian; Kruse, Kim; Haase, Claus; Skov, Søren; Nansen, Anneline; Syrbe, Uta
Abstract Background The aims of the present study were to determine the relationship between bone destruction and bone formation in the delayed-type hypersensitivity arthritis (DTHA) model and to evaluate the effect of receptor activator of nuclear factor κB ligand (RANKL) blockade on severity of arthritis, bone destruction, and bone formation. Methods DTHA was induced in C57BL/6 mice. Inflammation, erosive joint damage, and new bone formation were semiquantitatively scored by histology. Osteoclast activity was assessed in vivo, and messenger RNA (mRNA) expression of mediators of bone destruction and bone formation were analyzed by mRNA deep sequencing. Serum concentrations of tartrate-resistant acid phosphatase 5b, carboxy-terminal telopeptide I (CTX-I), matrix metalloproteinase 3 (MMP3), and serum amyloid P component (SAP) were determined by enzyme-linked immunosorbent assay. Anti-RANKL monoclonal antibody treatment was initiated at the time of immunization. Results Bone destruction (MMP3 serum levels, cathepsin B activity, and RANKL mRNA) peaked at day 3 after arthritis induction, followed by a peak in cartilage destruction and bone erosion on day 5 after arthritis induction. Periarticular bone formation was observed from day 10. Induction of new bone formation indicated by enhanced Runx2, collagen X, osteocalcin, MMP2, MMP9, and MMP13 mRNA expression was observed only between days 8 and 11. Anti-RANKL treatment resulted in a modest reduction in paw and ankle swelling and a reduction of serum levels of SAP, MMP3, and CTX-I. Destruction of the subchondral bone was significantly reduced, while no effect on bone formation was seen. Conclusions Anti-RANKL treatment prevents joint destruction but does not prevent new bone formation in the DTHA model. Thus, although occurring sequentially during the course of DTHA, bone destruction and bone formation are apparently not linked in this model.